Game Analysis on Epidemic Prevention and Resuming Production: Based on China’s Experience With COVID-19 - Zhuang, Weiqing; Wu, Qiong; Jiang, Ming; Ichiro, Nakamoto; Zhang, Tingyi; Yu, Xuelian (Frontiers in Psychology, 2021)
Since the outbreak of COVID-19, it became urgent to deal with the relationship between the prevention and control of the epidemic and the resumption of work and production. The purpose of this study is to observe and describe which approach seemed more important for the Chinese government and people, and how this trend evolved through time. To this end, a game model of resuming production and preventing the epidemic is constructed, using the evolutionary stable strategy (ESS). By combing China’s measures on epidemic prevention and resuming production during critical periods of epidemic outbreak, it is clarified that the present stage is considered a period of equal emphasis on both epidemic prevention and resuming production. Based on the dynamic between these two strategies and further theoretical research, present policies should equally focus on both preventive and controling measures as well as on the socioeconomic development.